Tasting notes - Belén López Arroyo; Lucia Sanz Valdivieso (Ibérica, 2022)
Tasting notes are professional texts used in different specialised contexts with the purpose of organising the taster’s sensory perceptions into attributes. There have been multiple studies focusing on the linguistic features of tasting notes, from their rhetorical structure to their use of metaphors; however, they have never been analysed using a combination of different, but complementary, linguistic perspectives, genre, and register. Our methodology, by employing these approaches, will outline comprehensively their features. In this paper, we will analyse the genre and register features of tasting notes in two different specialised languages in a corpus to find out whether there is a disciplinary variation or not. Additionally, we will describe, classify and contrast the way information is organised at different levels of analysis. Our results will be useful for scholars of genre, register and discourse studies, and for experts and technical writers in the olive oil and wine sectors.